Effectiveness of the RB51 vaccine in controlling brucellosis in adult beef cows - Fernandes, Carlos Antônio de Carvalho; Pereira, Gustavo Henrique Souza; Pereira, Jessica Ruiz; Alves, Daniele Cristina; Dias, Lucas Souza; Viana, João Henrique Moreira; Drumond, João (Frontiers in Veterinary Science, 2024)
IntroductionThe aim of this study was to compare the effectiveness of brucellosis control and reproductive performance using one or two doses of RB51 strain vaccine.MethodsThis experiment was conducted at two commercial beef farms (A, n = 477; and B, n = 673), which were selected due to their records of endemic brucellosis and a prevalence of 6 to 8% of seropositive cows. An initial serology screening (Day 0) was carried out in all cows using the Rose Bengal test (RB), and presumptive positive results were re-evaluated using a slow agglutination test with 2-mercaptoethanol (2-ME). Seropositive cows (64, 5.6%) were culled. Non-reactive cows were then randomly assigned into three experimental groups: G1, a single vaccination with RB51; G2, two doses of RB51 given 6 months apart; and G3 (control group), no vaccination. Serological tests were carried out on Days 90, 180, 270, and 360. In each evaluation, seropositive cows were removed. The variables related to occurrence of new infections and abortion, as well as those related to subsequent reproductive performance, were analyzed using the SAS software.Results and discussionSeropositive cows were still detected in both vaccinated and control groups at 90 days. However, no new infections were detected in G1 at 180 days or in G1 and G2 at 270 and 360 days, whereas new seropositive cows were diagnosed in all exams in G3 (control). Therefore, the cumulative number of new infections was lower in vaccinated than in control cows (0.2% and 0.0%, vs. 3.2% for groups G1, G2, and G3 respectively; p = 0.0002). In farm A the number of days open was greater in the control than in vaccinated groups (p < 0.05), and in farm B the pregnancy rate was lower in the control than in the group vaccinated once (p < 0.05). In summary, vaccination with RB51 in beef cows reduces the occurrence of new cases of brucellosis and improves the reproductive performance. There is no indication that a second immunization, six months after the first, enhances protection or reproductive efficiency.